Estimation of Prevalence of Psychological Distress and Constipation Among Patients Receiving Opioid Substitution Therapy - Hemaal Koul; Richa Mahajan; Burhan Hameed; Rajiv Kumar Gupta; Amani Ab Majeed Sofi (JK Science)
Background: Patients receiving Opioid Substitution Therapy (OST) often experience co-morbid conditions such as psychological distress, constipation and these complications can significantly impact the quality of life. Aims: This study aims to estimate the prevalence of psychological distress and constipation among patients undergoing OST. Material and Methods: This cross-sectional study was conducted in the Tertiary care hospital of Jammu over a period of six months. A total of 310 patients receiving OST were recruited through consecutive sampling. Socio-demographic data including age, gender, occupation, income, and level of education were collected using a structured scale. Psychological distress was assessed using the Kessler K6 scale, while constipation was evaluated using the Wexner scale. Data were analyzed using descriptive statistics and chi-square tests was used to determine factors associated with psychological distress and constipation. Results: All 310 participants were males and the mean age was 34.5 ± 8.6 years. The prevalence of moderate to severe psychological distress was 52%, with a mean K6 score of 18.2 ± 4.5. Constipation was prevalent in 43% of the participants, with a mean Wexner score of 11.3 ± 2.8. Conclusion: Psychological distress and constipation are frequently prevalent among patients receiving OST.